2004
DOI: 10.1038/sj.onc.1207354
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel SP3 binding site in the promoter of human IGFBP4 gene: role of SP3 and AP-1 in regulating promoter activity in CaCo2 cells

Abstract: Insulin-like growth factor binding protein 4 (IGFBP4/ BP4) gene expression plays an important role in the transition from proliferation to differentiation of a human colon cancer cell line, CaCo2. We recently cloned and identified multiple cis elements (including putative binding sites for activator protein 1 (AP-1) and specificity proteins (Sps) ) in the promoter of human BP4 gene, and measured a significant upregulation of the promoter activity in response to c-Jun. We therefore examined the role of the sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These data suggest that downregulation of IGFBP-4 expression in vascular smooth muscle plays a critical role in vascular growth response in normal and diseased states, by increasing the bioavailability of IGF-I (27). In addition to its antiproliferative action, IGFBP-4 has been correlated with differentiation of cancer cells (28).…”
Section: Biological Actions Of Igfbp-4mentioning
confidence: 89%
“…These data suggest that downregulation of IGFBP-4 expression in vascular smooth muscle plays a critical role in vascular growth response in normal and diseased states, by increasing the bioavailability of IGF-I (27). In addition to its antiproliferative action, IGFBP-4 has been correlated with differentiation of cancer cells (28).…”
Section: Biological Actions Of Igfbp-4mentioning
confidence: 89%
“…In this study, we conducted reporter gene assays using various lengths of IGFBP-4 and IGFBP-2 promoter elements. It has been shown that estrogen receptor-Sp1 complexes 47 or Sp3 (Sp3-binding site: Ϫ861 nucleotides to Ϫ856 nucleotides from the transcription start site) 48 regulates the promoter activity and thus the expression of human IGFBP-4. Our search for putative transcription factor-binding sites yielded two putative sites for thyroid transcription factor 1 (TTF-1), which is specifically expressed in lung airway epithelial cells, in the distal region of the human IGFBP-4 promoter (Ϫ1059 nucleotides to Ϫ1045 nucleotides, and Ϫ922 nucleotides to Ϫ908 nucleotides from the transcription start site).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Sp3, does not only act as a repressor, but can also act as a strong transcriptional activator. 61,64,65 With respect to the C4.4A gene, Sp3 clearly functions as an activator and not as a repressor.…”
Section: Discussionmentioning
confidence: 99%